The degree of employment of peer assessment and self-assessment to develop the written expression skill of school students in Jordan, according to the viewpoint of Arabic language teachers - Lafi, Eman (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to demonstrate the extent to which Arabic language teachers employ peer evaluation and self-evaluation to develop the skill of written expression among students in Jordanian schools and to highlight the main challenges they face in achieving this goal. Methods: The study used the descriptive method, employing a questionnaire designed with 34 items divided into five-point scales across five areas: peer evaluation of expression, self-evaluation of expression, training in peer evaluation and self-assessment criteria, challenges related to regionalism, and challenges associated with students, society, and parents. The study sample consisted of 97 teachers from public schools in the Directorate of Education of the Marka Brigade during the second semester of 2020/2021. Results: The study's results indicated that Arabic language teachers greatly employed peer evaluation and self-evaluation to develop the skill of written expression. There were no statistically significant differences observed in relation to variables such as experience and scientific qualification. Regarding the challenges, most of the paragraphs received significant ratings of difficulty. Conclusions: The study recommends establishing criteria and foundations for peer assessment evaluation and self-assessment, conducting practical training courses on their implementation, and encouraging teachers to adopt modern evaluation strategies that enhance the development of written expression skills.